Global citizenship education in the global South : educators' perceptions and practices - Bosio, Emiliano; Waghid, Yusef (Moral development and citizenship education, 2023)
"This volume presents a critical discussion that brings contemporary academic debate about 'southern theory' to Global Citizenship Education (GCE). It situates the discussion around GCE in the Global South within a critical and post-colonial paradigm informed by the values and knowledge of critical pedagogy ingrained in social justice. Global Citizenship Education in the Global South invites the reader into chapters written by educators exploring, analysing, and celebrating ideas and concepts on GCE in the Global South. The book is presented as a pedagogical tool for discussion that invites educators to reflect critically on the possible origins and implications of GCE discourses they are exposed to. The book is designed with the intent to contribute towards the possibility of imagining a 'yet-to-come' critical-transformative and post-colonial and value-creating GCE curriculum beyond a west"-- Provided by publisher.